2012
DOI: 10.1210/en.2011-1930
|View full text |Cite
|
Sign up to set email alerts
|

Caffeine Inhibits EGF-Stimulated Trophoblast Cell Motility through the Inhibition of mTORC2 and Akt

Abstract: Impaired trophoblast invasion is associated with pregnancy disorders such as early pregnancy loss and preeclampsia. There is evidence to suggest that the consumption of caffeine during pregnancy may increase the risk of pregnancy loss; however, little is known about the direct effect of caffeine on normal trophoblast biology. Our objectives were to examine the effect of caffeine on trophoblast migration and motility after stimulation with epidermal growth factor (EGF) and to investigate the intracellular signa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 41 publications
0
8
0
Order By: Relevance
“…In non-glioma cells, caffeine decreases invasion of human leukemia U937 cells through the Ca 2+ /ROS-mediated suppression of ERK/c-fos and activation of p38 MAPK/ c-jun pathways [17]. Furthermore, caffeine inhibits the motility of extra-villous trophoblasts by blocking the mammalian target of rapamycin complex 2 and Akt [18]. Here, caffeine treatment impairs focal adhesion protein activity that is blocked by ROCK activation, which leads to the down-regulation of both adhesion ability and migration in glioma cells.…”
Section: Discussionmentioning
confidence: 99%
“…In non-glioma cells, caffeine decreases invasion of human leukemia U937 cells through the Ca 2+ /ROS-mediated suppression of ERK/c-fos and activation of p38 MAPK/ c-jun pathways [17]. Furthermore, caffeine inhibits the motility of extra-villous trophoblasts by blocking the mammalian target of rapamycin complex 2 and Akt [18]. Here, caffeine treatment impairs focal adhesion protein activity that is blocked by ROCK activation, which leads to the down-regulation of both adhesion ability and migration in glioma cells.…”
Section: Discussionmentioning
confidence: 99%
“…SGHPL-4 motility in response to endostatin and angiogenin was assessed as previously described using time-lapse microscopy (Grant et al , 2012). SGHPL-4 cells were seeded in Hams F10 media supplemented with 10% (v/v) FBS before overnight incubation in Hams F10 media supplemented with 0.5% (v/v) FBS.…”
Section: Methodsmentioning
confidence: 99%
“…SGHPL-4 cells were then lysed in Radio-Immunoprecipitation Assay buffer containing a protease inhibitor cocktail of aprotinin (60 µg/ml), phenylmethylsulfonyl fluoride (1 mM) and sodium orthovanadate (1 mM). Western blotting was then performed as previously described (Grant et al , 2012) using rabbit anti-phospho-Akt Ser473 (1/2500 dilution, Cell Signalling Technology, Hertfordshire, UK), rabbit anti-phospho-ERK 1/2 (1/1000 dilution, Cell Signalling Technology), mouse anti-phospho-FAK (pY937, BD Biosciences, Oxford, UK) or mouse anti-α-tubulin (1/10 000 dilution, Abcam, Cambridge, UK). Western blots were scanned and the integrated density of each band determined using Image-J software (version 1.47d).…”
Section: Methodsmentioning
confidence: 99%
“…In 2014, an ex vivo perfusion of the human placenta proved that caffeine freely crosses the placenta by passive diffusion, as previously reported, regardless the dose used [67]. Using an in vitro model, Grant et al [68] observed that caffeine inhibits EGF-stimulated trophoblast invasion and motility, which could lead to pregnancy disorders such as early pregnancy loss and preeclampsia. Thus, according to these authors, the consumption of caffeine should be discouraged.…”
Section: Caffeine Intake During Pregnancy: What Are the Real Evidences?mentioning
confidence: 81%
“…In vitro and ex vivo perfusion models, like cultured human placental cells, have also been explored in an attempt to establish a safe dose of caffeine consumption during pregnancy [67][68][69]. In 2014, an ex vivo perfusion of the human placenta proved that caffeine freely crosses the placenta by passive diffusion, as previously reported, regardless the dose used [67].…”
Section: Caffeine Intake During Pregnancy: What Are the Real Evidences?mentioning
confidence: 96%